Mastication as a protective factor of the cognitive declinein adults: A qualitative systematic review - Chuhuaicura, Priscila; Dias, Fernando José; Arias, Alain; Lezcano, María Florencia; Fuentes, Ramón
A relationship between masticatory function and cognition has been reported. It is proposed that mastica-tion changes the blood ﬂow stimulating the perfusion/oxygenation of the brain. This literature review analysed the rela-tion between mastication as a protective factor of the cognitive decline and the changes produced at brain level in adultsassociated with the brain blood ﬂow. Materials and methods: A systematic review was performed according to the ‘Pre-ferred Reporting Items for Systematic Reviews and Meta-Analyses’ (PRISMA) criteria in PubMed/MEDLINE, Web ofScience, Scopus and Embase. Primary studies were included with no limit on the publication date, conducted on humans,and that established a relation between mastication, brain blood ﬂow and cognitive functions in adult patients. Results:Nine clinical descriptive studies were selected and qualitatively analysed. The collected data suggest the greatest brainareas activated during mastication were the frontotemporal cortex, the caudate nucleus and the thalamus, revealing apositive correlation between chewing intensity and perfusion of the principal trigeminal nucleus. The increase in cerebralblood ﬂow was measured by a local vasodilator effect resulting in increased neuronal metabolism in the region linked tolearning and memory. In addition, partially edentulous participants had a marked prefrontal deactivation when theychewed without a prosthesis and presented a decrease in masticatory activity. Conclusion: Masticatory function may actas a protective factor in those patients with cognition impairment and neurodegenerative diseases, suggesting some mech-anisms among which is the increase of cerebral blood ﬂow.